Influence of ultrasound focus depth on the association between echo intensity and intramuscular adipose tissue. Issue 5 (2nd September 2022) - Fukumoto, Yoshihiro; Taniguchi, Masashi; Hirono, Tetsuya; Yagi, Masahide; Yamagata, Momoko; Nakai, Ryusuke; Asai, Tsuyoshi; Yamada, Yosuke; Kimura, Misaka; Ichihashi, Noriaki
Abstract: Introduction/Aims: Attenuation of the ultrasound (US) wave is a serious limitation of echo intensity (EI) on B‐mode US. The aim of this study was to determine whether the focus depth of US images influences the depth‐dependent attenuation of EI and the relationship between EI and intramuscular adipose tissues (IntraMAT). Methods: The rectus femoris (RF) and vastus intermedius (VI) of the right thigh were studied in 135 adults (92 older, 43 younger). The EI on US images was measured at three focus depth conditions: top of the image, center of the RF, and center of the VI. The depth of the region of interest (ROI) was measured. IntraMAT was calculated using water and fat images based on the two‐point Dixon technique with a 3.0‐T magnetic resonance imaging scanner. Results: The correlation between EI and IntraMAT was stronger in the focus RF and VI conditions than in the focus top condition and stronger for RF than for VI. The depth of the ROI influenced the IntraMAT‐adjusted residual EI more in the focus top condition than in the focus RF and VI conditions, and influenced VI more strongly than it did RF. Discussion: By mitigating EI attenuation, EI with a focus depth adjusted to the ROI reflected IntraMAT more accurately than that without adjustment. However, it may not completely prevent the potential influence of depth‐dependent attenuation of EI, especially for deeper muscles such as the VI.